Penilaian Prestasi Pekerja Pada Bidang Penanganan Prasarana Dan Sarana Umum Menggunakan Algoritma Decision Tree C4.5 - I Gusti Ngurah Adytya; Budi Sudrajat (LPPM UBHINUS MALANG, 2025)
One way that should be finished to decide representative execution is to decide the worth that has been gotten equitably founded on the discipline measures of participation, obligation regarding finishing work, and consistence with commitments and denials, utilizing the C4.5 choice tree calculation. The data studied was the Worker Performance Evaluation Form with a total of 108 workers, in 2023-2024 based on certain criteria with the data selected being 96 active workers. This data has several criteria, namely attendance discipline, responsibility for completing work, and compliance with obligations and prohibitions. The main aim of this writing is to determine employee performance from each criterion. The C4.5 decision tree algorithm can assist in the decision-making process regarding improving the performance and training of workers in the field of handling public infrastructure and facilities. You can see the results of the research that has been carried out as training data, the gain and entrophy values ​​have been calculated. In the first partition, the highest gain value was obtained for Compliance with Obligations and Prohibitions with a value of 0.489943 and the smallest was Responsibility for Completion of Work with a value of 0.172824. This algorithm can be used to determine employee performance as a candidate for employee performance which will be determined by the relevant agency.